PERBANDINGAN PENGARUH PENAMBAHAN SERAT BENDRAT LURUS (STRAIGHT) DENGAN SERAT BENDRAT BERKAIT (HOOKED) TERHADAP PERILAKU BETON DENGAN BEBAN TEKAN BERULANG - Faizah, Poppy Nitiranda; Purwanto, Eddy; Irianti, Laksmi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
In this research, the concrete mixture is added by the material of straight and hooked wire bendrat fibers. This addition aimed to study and compare the effect of adding bendrat fiber straight and hooked to the compressive strength, tensile strength and flexural strength in normal quality concrete with 0.75% fiber concentration and aspect ratio 60 with repeated press load. The test specimen compressive and  tensile strength in the form of cylinders with a diameter of 15 cm and height 30 cm and the flexural strength test specimen in the form of beam with a length of 60 cm, width 15 cm and height 15 cm. Testing is done after 28 days. Concrete with additional hooked bendrat fiber is more able to withstand fatigue due to repeated load that generates more experienced loading intervals until concrete destroyed, the compressive strength at the 13th interval, 14th tensile and 6th flexural. The compressive strength, tensile and flexural maximum split value occurred in the concrete with the addition of hooked bendrat fiber. However, the value did not increase significantly between the variations of straight bendrat fiber with hooked bendrat fiber. The maximum compressive strength in the hooked bendrat fiber of 34.5189 MPa, tensile strength of 3.2067 MPa and flexural strength of 8.9380 MPa.______ Key words:   bendrat fiber, repeated press load, compressive strength, tensile strength, flexural strength.